Determinants of unintended pregnancy among women in Nepal - Adhikari, Ramesh; Soonthorndhada, Kusol; Prasartkul, Pramote (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aim: This study aims to determine the factors influencing unintended pregnancy among married women in Nepal Methods: This paper reports on data drawn from Nepal Demographic and Health Survey (DHS), 2001 which is a nationally representative sample survey. The analysis is restricted to the currently pregnant women at the time of survey. Logistic regression was used to assess the net effect of several independent variables on unintended pregnancy. The factors leading to unintended pregnancy were also predicted by using some significant variables in the model. Results: More than two-fifth of the respondents (41%) reported that their current pregnancies were unintended. The results indicate that age, age at first marriage, religion, exposure to radio and knowledge of family planning (FP) methods were key predictors of unintended pregnancy. Experience of unintended pregnancy augments along with the women’s age. Similarly, increase in age at first marriage reduces the likelihood of unintended pregnancy among women. Those who were exposed to radio were less likely (odds ratio, 0.65) to have unintended pregnancy compared to those who were not. Those women who had higher level of knowledge about FP methods were 40% less likely to experience unintended pregnancy compared to those having lower level of knowledge. Conclusion: One of the important factor contributing to high level of maternal and infant mortality is unintended pregnancy. Programs should intend to reduce unintended pregnancy by focusing on all these identified issues so that infant and maternal morbidity and mortality as well as abortion will be decreased and the overall health of the family could be improved. DOI: http://dx.doi.org/10.3126/njog.v3i2.10828   Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 26-34